Isolation from individual A/J mice of anti-rho-azophenylarsonate antibodies bearing a cross-reactive idiotype (The Rockefeller University Press, 1975)
Immuization of A/J mice with a KLH-p-azophenylarsonate conjugate induces the formation of antihapten antibodies, some of which share idiotypic specificity common to all recipients. The subpopulation carrying the idiotype generally comprises 20-70% of the total antibody content. Large quantities of antihapten antibody (occasionally over 100 mg) were obtained from individual mice through the induction of an ascites fluid. This facilitated isolation of antibodies with the cross- reactive idiotype by isoelectric focusing. Most of this subpopulation has pI values between 6.65 and 6.95 and essentially all is of the IgG1 subclass. Two peaks, near pI 6.7 and 6.9, were frequently observed. Upon refocusing, the protein artifact of the procedure, but indicates microheterogeneity. The antibodies in the two peaks were found to be idiotypically identical by measurements of cross-inhibition. Preliminary studies have indicated that it is feasible to initiate investigations of primary structure with antibodies from individual inbred mice.